Pregnancy from mosaic embryo transfer: genetic counseling considerations. Issue 2 (April 2021) - Chen, Kelly; Darcy, Diana; Boyd, Allison
Abstract : Purpose of review: The transfer of mosaic embryos during an IVF procedure is becoming more common. There is limited information regarding the outcomes for such transfers, making it difficult to establish best practices for prenatal counseling of patients considering transfer of mosaic embryos. In addition, genetic counseling may be delivered by different providers in the preimplantation and pregnancy timeframes which can contribute to inconsistent information. Recent findings: There are many types of aneuploid results from preimplantation genetic testing for aneuploidy (PGT-A), with mosaicism being a possibility. Recent studies have reported normal prenatal diagnostic results, pregnancy and birth outcomes with mosaic embryo transfers. Reproductive and prenatal society guidelines recommend diagnostic testing in pregnancy following a mosaic result by PGT-A. Prenatal genetic counseling providers should consider the available information from the PGT-A result, emphasizing the benefits and limitations of each available prenatal test in detecting the fetal chromosome complement. Summary: While transfer of mosaic embryos can allow couples without euploid embryos to have a chance of a viable pregnancy, further studies are necessary to better guide this decision-making. In addition, better coordination between reproductive providers and prenatal providers could improve prenatal care.